Modern language olympiad: unleashing potentials for 21st century skills / Ahmad Mazli Muhammad … [et al.] - Muhammad, Ahmad Mazli; Boon Awang, Mohd Hassan; Mohamad Aris, Nurbaya; Ahmad Kamil, Maisarah; Druckman, Zachariah Aidin (Universiti Teknologi MARA, 2020)
The challenge of becoming employable 21st century graduates to meet current industry demands was the basis of this innovation. With the aim to equip a group of students with soft skills on one hand, and another with industry-specific communicative abilities on the other, the Modern Language Olympiad (MLO) was established under Akademi Pengajian Bahasa, UiTM Shah Alam, as the first multi-language competition held internationally that is fully student-led. Five categories of competitions were designed with close engagement with the industry, which were strategic storytelling, idea pitching, versatile presenting, and radio drama across three languages (English, Bahasa Melayu, and Arabic) from 29 October to 2 November 2019. Preparations to conduct this international competition commenced a year before that. In total, 330 participants from 11 public universities, 6 private universities and 4 foreign universities and 10 UiTM branch campuses participated in the event, which was run by 40 student committee and 100 student volunteers, guided by 30 academic advisors. A total of 40 judges from the industry were involved in the competitions. The event, which amassed a total profit of RM58,416.45, managed to develop the student committee’s critical thinking, problem solving, time management, project management, and budgeting skills, while the participants gained immeasurable benefits in enhancing their communication skills through feedback from the industry and by observing others. This innovation is a step forward to improve students’ soft skills and communication skills using the two-pronged approach through running a student-led, student-driven, wide-scale international event.